(untitled) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-4-45-55 The features of the realization of the linguistic and cultural potential of neologisms about vaccination against COVID-19 are under the analysis in the German-language media discourse. News articles about vaccination are analyzed among the period from 2021 to 2022. According to the article, vaccinologisms reflect the national and cultural specifics of Austria, Germany and Switzerland. Such vocabulary is used to describe points for vaccination and to promote vaccination in society. Results of the research suggest that vaccinologisms are used to form a positive opinion about vaccination in the German-speaking society. Key words: neologisms, intercultural aspect, vaccination, COVID-19, German, media discourse